Collins primary literacy: pupil book 1c - Hiatt, Kay; Stones, Brenda (Collins Educational London, 2008)
Pupil Book 1C covers a wide variety of text types and topics, and provides engaging activities to help you deliver the objectives of the renewed Framework.